2006
DOI: 10.1068/p5547
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing during Face Recognition: The Effects of Familiarity, Inversion, and Morphing on Scanning Fixations

Abstract: Where we make ocular fixations when viewing an object likely reflects interactions between 'external' object properties and internal 'top-down' factors, as our perceptual system tests hypotheses and attempts to make decisions about our environment. These scanning fixation patterns can tell us how and where the visual system gathers information critical to specific tasks. We determined the effects of the internal factors of expertise, experience, and ambiguity on scanning during a face-recognition task, in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
234
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(284 citation statements)
references
References 39 publications
42
234
7
1
Order By: Relevance
“…This would explain the narrowing of the perceptual field in inverted faces for which features have to be processed sequentially and independently because of the loss of holistic processing (Rossion, 2009). This featural processing requires viewers to change their face scanning pattern toward more fixations on specific features (Barton et al, 2006;Hills et al, 2012) in order to collect all relevant facial information to do the task at hand (e.g. recognize the identity).…”
Section: Inhibition Of Foveated Features By Perifoveal Features Ensurmentioning
confidence: 99%
See 1 more Smart Citation
“…This would explain the narrowing of the perceptual field in inverted faces for which features have to be processed sequentially and independently because of the loss of holistic processing (Rossion, 2009). This featural processing requires viewers to change their face scanning pattern toward more fixations on specific features (Barton et al, 2006;Hills et al, 2012) in order to collect all relevant facial information to do the task at hand (e.g. recognize the identity).…”
Section: Inhibition Of Foveated Features By Perifoveal Features Ensurmentioning
confidence: 99%
“…Eye tracking studies suggest that regardless of task and initial fixation position, participants tend to fixate on or close to the eye region (e.g. Arizpe et al, 2012;Barton et al, 2006;Janik et al, 1978). Eyes are also the most attended feature regardless of face familiarity (Heisz & Shore, 2008) and this preference is seen in infants (Maurer, 1985), with a clear sensitivity to gaze direction already present at birth (Batki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…eyes, nose and mouth). A few eye-tracking studies have revealed that, in comparison with unfamiliar faces, viewing of familiar (famous, familiarized or personally familiar) faces is associated with fewer fixations and a shorter scanning duration (Barton, Radcliffe, Cherkasova, Edelman, & Intriligator, 2006;Heisz & Shore, 2008), or is accompanied by directing sequential fixations to different local facial regions (van Belle, Ramon, Lefèvre, & Rossion, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For human faces, the judgement of approachability corresponds closely to trustworthiness/valence rating (Vernon et al, 2014), and the perceived facial expression is crucial for forming an impression of approachability (Willis, Palermo, & Burke, 2011;Vernon et al, 2014). Considering that humans would name familiar faces faster than unfamiliar ones (Bar & Bierderman, 1998) and demonstrate proficient gaze pattern in the viewing of more-experienced familiar faces (Barton et al, 2006;Heisz & Shore, 2008), we hypothesized that dog-owners may use less viewing time and adopt a more 'efficient' gaze strategy (e.g., fewer number of fixations and fixation allocation at task-relevant informative facial regions) to judge the approachability of dog faces.…”
Section: Introductionmentioning
confidence: 99%
“…There is no significant effect of talker variability on either the overall number of fixations or the median duration of fixations (p> .05). Detailed results for each region of interest (ROI) are presented below for the overall number of fixations and fixation durations, and for the number of first and second fixations in each trial.In previous studies looking at gaze behavior during face perception, specifically in studies of audiovisual speech perception (Everdell, Marsh, Yurick, Munhall & Paré, 2007; VatikiotisBateson et al, 1998;Paré et al, 2003) and identity judgment (Henderson et al, 2005;Barton et al, 2006;Althoff & Cohen, 1999), there is a preference to fixate the talker's right eye more often than the left eye. We wanted to see if this preference to fixate the right eye also occurred in the current study.…”
mentioning
confidence: 99%